Eksitensi Tari Piring Grup Kalinco di Desa Rambah Tengah Utara Kecamatan Rambah Kabupaten Rokan Hulu - Putri Rahmayati; Yahyar Erawati (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Kalinco Group Plate Dance in Rambah Tengah Utara Village, Rambah District, Rokan Hulu Regency. The theory used by researchers in Existence is Jazuli (2016:52) which explains that there is space and time: space includes value systems, performance and events. Time includes the process of creation. The method used by researchers is qualitative research using descriptive methods, namely by collecting accurate data from sources regarding the existence of the Kalinco Group Piring Dance to improve research results and make it easier to formulate the problem. The results of this research are found in space and time. The existence of space is based on the value system in this plate dance, namely in this dance the social value of mutual cooperation is found in the movements when the two men are in the middle of the dancers. One man rides another man so that cooperation between dancers is formed. The existence of space related to the performance of this plate dance is that the performance of the plate dance begins with the dancer entering the stage with a plate on the palm of his hand. The existence in question is not a place where an object is located, but the word existence contains the meaning of the existence of an activity that is continuously carried out, so that the activity continues to run smoothly (Hanum, Ritawati and Satria, 2022). This traditional art is very closely related, especially to older people, which still survives today. Older people think that this traditional art is an art that needs to be preserved, so they hope that the traditional art of Masukkiri will survive and continue to exist, however, the younger generation thinks that Masukkiri is out of date and only for the old (Jannah, Effendi and Susanto, 2021).